Social Networks and Mobility in Time and Space: Integration Processes of Burmese Karen Resettled Refugees in Sweden. (19th February 2019) - Suter, Brigitte
Abstract: Although there are exceptions, refugees from protracted refugee situations generally experience an overall slower integration process into the new country than other refugees and immigrants. Often the circumstances in the refugee camps, including lacking education and social networks, are used to explain this. This article looks at the post-resettlement integration process of Burmese Karen refugees in Sweden through a capital approach. Consequently, the analysis is concerned with the accumulation of resources—such as social networks—both in the pre- and post-resettlement contexts. Mobility is acknowledged as a decisive factor in this process and, as such, mobility practices from both before and after resettlement are highlighted to better understand the refugees' social, cultural and economic embeddedness. As this article argues, social and cultural capital acquired before resettlement is of crucial importance to create social networks after resettlement and hence to the overall integration process in Sweden.